Between Sympathy and Hostility: Acehnese Attitudes towards Rohingya Refugees - Bahri, M. Irvanni; Kismawadi, Early Ridho; Agustina, Tri Siwi (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
This research seeks to explore the perspectives of the Acehnese community regarding Rohingya refugees, emphasizing the contrast between compassion and animosity. The study utilizes a content analysis approach, drawing on secondary data from local Acehnese online media and relevant literature concerning refugee matters in Indonesia from 2022 to 2024.The findings reveal two predominant perspectives: sympathy driven by humanitarian compassion and Islamic solidarity, and hostility arising from concerns over socio-economic burdens and anti-immigrant sentiments. Sympathy is reflected in calls for aiding war victims, while hostility is linked to fears of resource competition and cultural tensions. The implications of this research are twofold. First, it highlights the necessity for culturally sensitive interventions to address misconceptions and fears that foster hostility. Second, it emphasizes the importance of public education campaigns and community engagement to strengthen values of compassion and solidarity. These findings provide valuable insights for policymakers and humanitarian organizations to develop strategies that balance humanitarian assistance with sustainable socio-economic policies, ensuring harmonious coexistence between host communities and refugees.